PEMENUHAN HAK ATAS PENDIDIKAN LAYAK BAGI ANAK HAMIL SEBELUM MENIKAH DALAM PERSPEKTIF JENDER : Fulling The Right To Decent Education For Pregnant Children Before Marriage From A Gender Perspective - Wyngky Angeli Esaputri; Wahyuni Retno Wulandari (Reformasi Hukum Trisakti, 2026)
The fulfillment of educational rights for children who become pregnant before marriage remains a frequently occurring problem in practice, even though it is normatively regulated in various laws and regulations in Indonesia. Pregnancy before marriage is often a reason, particularly for girls, to choose to drop out of school. Legally, however, a child who becomes pregnant before marriage is still considered a child and retains the right to welfare in their life. The problem of this study aims to analyze the fulfillment of proper educational rights for children who become pregnant before marriage from a gender perspective, as well as to examine legal regulations regarding the fulfillment of proper educational rights for pregnant children in ensuring that these rights are met. The research method used is normative legal research with legislative and conceptual approaches. The results and conclusion of the study indicate that although the law guarantees children's educational rights without discrimination, in practice there are still obstacles that cause pregnant children to lose their right to education. Therefore, an integrated model for fulfilling the right to education is needed between the state, schools, and parents so that children's right to education is maintained, along with guarantees for their welfare and development.